A review of deubiquitinases and thier roles in tumorigenesis and development - Liang, Xian-Wen; Wang, Sheng-Zhong; Liu, Bing; Chen, Jia-Cheng; Cao, Zhi; Chu, Feng-Ran; Lin, Xiong; Liu, Hui; Wu, Jin-Cai (Frontiers in Bioengineering and Biotechnology, 2023)
Ubiquitin is a small protein that can be added onto target protein for inducing target degradation, thereby modulating the activity and stability of protein. Relatively, deubiquitinases (DUBs), a class catalase that can remove ubiquitin from substrate protein, provide a positive regulation of the protein amount at transcription level, post-translational modification, protein interaction, etc. The reversible and dynamic ubiquitination-deubiquitination process plays an essential role in maintaining protein homeostasis, which is critical to almost all biological processes. Therefore, the metabolic dysregulation of deubiquitinases often lead to serious consequences, such as the growth and metastasis of tumors. Accordingly, deubiquitinases can be served as key drug targets for the treatment of tumors. The small molecule inhibitors targeting deubiquitinases has become one of the hot spots of anti-tumor drug research areas. This review concentrated on the function and mechanism of deubiquitinase system in the proliferation, apoptosis, metastasis, DNA damage repair and autophagy of tumor cells. In addition, the research status of small molecule inhibitors of specific deubiquitinases in tumor treatment is introduced, aiming to provide reference for the development of clinical targeted drugs.